DIGITALIZATION AND ITS IMPACT ON INDIAN TAXATION (CAHIERS MAGELLANES-NS, 2024)
After Globalization, the world is shifting towards digitalisation. The business, trade and commerce have come over to this digital platform. Without a doubt, this digital platform is very boon for business houses and as well as it has also given a lot of relief to the people around. But with that, it has affected the taxation of the country. The enhanced technology of digitalization has given evaders several creative methods for tax evasion.Based on this the researcher has divided the research paper into the following:The first part of the research paper is “Introduction” which gives a general idea of the topic that is digitalization and its impact on Indian Taxation.The second part of this paper talks about the meaning of digitalization and taxation.The third part is the historical perspective, which gives a glance at the history of digitalization and taxation.The fourth part is the main part of the whole paper in which the concern has been raised regarding issues in Indian taxation because of digitalization.The fifth part of the paper gives the legal provisions for digitalization and taxation.The sixth part is the concluding part of the whole research work in which suggestions and international perspectives has been taking in to account to overcome the issue